Consumption of Goats’ Milk Protects Mice From Carbon Tetrachloride-Induced Acute Hepatic Injury and Improves the Associated Gut Microbiota Imbalance - Zhang, Jiachao; Wang, Zhaoxia; Huo, Dongxue; Shao, Yuyu (Frontiers in Immunology, 2018)
Drugs used to treat liver diseases have serious side effects; it is important to search for safe functional foods with hepatoprotective functions and few side effects. In this study, potential hepatoprotective effects of goats’ milk and cows’ milk on mice with CCl4-induced acute hepatic injury were evaluated. We also elucidated the role of goats’ and cows’ milk on the regulation of CCl4-induced gut microbiota imbalance. In mice with liver damage induced by CCl4, administration of goats’ milk for 7 days prior to injection of CCl4 had beneficial effects on the indicators of liver damage within 1 day: the area of liver necrosis was small; activity of alanine transaminase (ALT) and aspartate transaminase (AST) and expression of the genes CYP2E1 and TNF-α were lower than that of model group of mice. By 7 days after CCl4 injection, there were no significant differences in liver damage indicators (ALT, AST, malondialdehyde, superoxide dismutase, and glutathione) between the goats’ milk group, which continued to receive goats’ milk, and the untreated control group of mice showing that goats’ milk continued to protect against liver damage. Throughout the entire experiment, the community of gut microbes from mice in the goats’ milk treatment was more similar to the untreated control group than to the cows’ milk group and the model group, indicating that intake of goats’ milk prior and post-CCl4 injection effectively prevented and alleviated the intestinal microbial disorder that caused by CCl4 in mice. Our research suggests that goats’ milk could be developed as a potential functional food to prevent/protect against liver injury.